Genetic variants of calcium and vitamin D metabolism in kidney stone disease - Howles, Sarah A.; Wiberg, Akira; Goldsworthy, Michelle; Bayliss, Asha L.; Gluck, Anna K.; Ng, Michael; Grout, Emily; Tanikawa, Chizu; Kamatani, Yoichiro; Terao, Chikashi; Takahashi, Atsushi; Kubo, Michiaki; et al. (Nature communications, 2019)
Kidney stone disease (nephrolithiasis) is a major clinical and economic health burden with a heritability of ~45–60%. We present genome-wide association studies in British and Japanese populations and a trans-ethnic meta-analysis that include 12,123 cases and 417,378 controls, and identify 20 nephrolithiasis-associated loci, seven of which are previously unreported. A CYP24A1 locus is predicted to affect vitamin D metabolism and five loci, DGKD, DGKH, WDR72, GPIC1 , and BCR , are predicted to influence calcium-sensing receptor (CaSR) signaling. In a validation cohort of only nephrolithiasis patients, the CYP24A1- associated locus correlates with serum calcium concentration and a number of nephrolithiasis episodes while the DGKD- associated locus correlates with urinary calcium excretion. In vitro, DGKD knockdown impairs CaSR-signal transduction, an effect rectified with the calcimimetic cinacalcet. Our findings indicate that studies of genotype-guided precision-medicine approaches, including withholding vitamin D supplementation and targeting vitamin D activation or CaSR-signaling pathways in patients with recurrent kidney stones, are warranted. Kidney stones form in the presence of overabundance of crystal-forming substances such as Ca 2+ and oxalate. Here, the authors report genome-wide association analyses for kidney stone disease, report seven previously unknown loci and find that some of these loci also associate with Ca 2+ concentration and excretion.